Early Development of the Gonadotropin-Releasing Hormone Neuronal Network in Transgenic Zebrafish - Zhao, Yali; Lin, Meng-Chin; Farajzadeh, Matthew; Wayne, Nancy (Frontiers in Endocrinology, 2013)
Understanding development of gonadotropin-releasing hormone (GnRH) neuronal circuits is fundamental to our understanding of reproduction, but not yet well understood. Most studies have been focused on GnRH neurons located in the hypothalamus and preoptic area (POA), which directly regulate the pituitary-gonadal axis. In zebrafish (Danio rerio), two forms of GnRH have been identified: GnRH2 and GnRH3. GnRH3 neurons in this species plays two roles: hypophysiotropic and neuromodulatory, depending on their location. GnRH3 neurons in in the ventral telencephalon, POA and hypothalamus control pituitary-gonadal function; in other areas (e.g., terminal nerve), they are neuromodulatory and without direct action on reproduction. To investigate the biology of GnRH neurons, a stable line of transgenic zebrafish was generated in which the GnRH3 promoter drives expression of a bright variant of green fluorescent protein (Emerald GFP, or EMD). This provides unprecedented sensitivity in detecting and imaging GnRH3 neurons during early embryogenesis in the transparent embryo. Using timelapse confocal imaging to monitor the time course of GnRH3:EMD expression in the live embryo, we describe the emergence and development of GnRH3 neurons in the olfactory region, hypothalamus, POA, and trigeminal ganglion. By 50 hours post fertilization, these diverse groups of GnRH3 neurons project broadly in the central and peripheral nervous systems and make anatomical connections with each other. Immunohistochemistry of synaptic vesicle protein 2 (a marker of synaptic transmission) in this transgenic model suggests synaptic formation is occurring during early development of the GnRH3 neural network. Electrophysiology reveals early emergence of responsiveness to the stimulatory effects of kisspeptin in terminal nerve GnRH3 neurons. Overall, our findings reveal that the GnRH3 neuronal system is comprised of multiple populations of neurons as a complicated network.